Antimicrobial efficacy of aqueous ozone in combination with short chain fatty acid buffers. Issue 1 (March 2020) - Britton, Holly C.; Draper, Michael; Talmadge, James E.
Summary: Background: Mitigating surface contamination by microbes such as S. aureus, Salmonella enterica, or Klebsiella pneumoniae, is an ongoing problem in hospital and food production environments. Aim: To determine whether addition of buffering solution to source water used for manufacture of aqueous ozone increases ozone efficacy against ozone-resistant bacterial species. Methods: Antimicrobial effects of aqueous ozone were studied in combination with acetate, propionate, or butyrate short chain fatty acids (SCFA) as well as citrate or oxalate buffer formulations against Staphylococcus aureus on glass coupons. Aqueous ozone combined with an acetate buffer was also evaluated against Salmonella enterica and Klebsiella pneumoniae . Findings: The acetate, propionate, and butyrate buffered aqueous ozone combinations had a significant 3–4 log reduction of S. aureus ( P <0.05) colony forming unit (CFU), while citrate or oxalate buffered aqueous ozone, although statistically significant versus buffer alone, had less activity. Treatment of S. aureus, S. enterica, or K. pneumoniae with acetate buffered aqueous ozone also resulted in a 4 log or greater reduction in CFUs post-treatment for all three species, versus treatment with water alone. Conclusions: All buffer systems tested had a significantly greater reduction in CFUs following treatment with the combination of buffer and ozone, compared to treatment with buffer or ozone individually, which has not been previously reported for hard surfaces. These results suggest that SCFA buffered ozone has greater anti-bacterial activity relative to either agent alone, and the activity is independent of the buffering activity. Thus, these formulations have potential to sanitize without residues, using an environmentally conscious formulation.